PERBANDINGAN PREDIKSI FINANCIAL DISTRESS DENGAN MENGGUNAKAN MODEL ALTMAN, SPRINGATE DAN OHLSON - Fairuz Zabady Zainal Abidin Putera; Fifi Swandari; Dian Masita Dewi (JWM (JURNAL WAWASAN MANAJEMEN), 2016)
The lowering of coal price and the uncertainty of world oil prices affect the high operational costs of coal enterprises. The Continuous lowering of coal prices causes financial distress. Financial distress is defined as financial condition before the bankcruptcy.The purpose of this research are to predict and compare the financial distress among the models of Altman, Springate and Ohlson at coal mining company listed on the Indonesia Stock Exchange in the period of 2008 - 2014. This type of research is included in a comparative. The population are the coal companies financial statements listed on the Indonesian Stock Exchange (BEI) in the period 2008-2014. The sampling with used purposive sampling which acquired 7 companies. Data analysis used Altman, Springate and Ohlson’s models. The hypothesis is tested Kruskal-Wallis test. The results of research showed that Springate’s model has better accuracy than Altman model and Ohlson model. Results hypothesis testing with the Kruskal-Wallis test concluded there were no differences among the financial distress the model Altman, Springate and Ohlson models at coal mining companies in the Indonesia Stock Exchange in the period 2008-2014.